Tindak Pidana di Bidang Perbankan dalam Transaksi Perdagangan Luar Negeri dengan Menggunakan Letter Of Credit - I Wayan Dodi M. Putra; Ni Luh Made Mahendrawati; Ni Komang A. Styawati (Jurnal Konstruksi Hukum, 2022)
Letter of Credit/LC is an interbank payment transaction instrument whose legal arrangements have been established both nationally and internationally. In this study, the writer wants to know how the regulation of criminal acts in the banking sector against foreign transactions through letters of credit, and the criminal sanctions that make the issuing bank a victim in foreign trade transactions using the letter of credit , uses this type of normative research. sources of primary, secondary, and tertiary rules. This thesis uses the type of search, recording and documentation Analysis of legal sources is carried out systematically using legal arguments and the results are presented descriptively. The conclusion is that the regulation of foreign trade crimes through Letter of Credit is regulated in UPC-DC600 and PP No. 1/1982 as well as Law No. 10/1998 on banking. Sanctions for violating foreign transactions through a Letter of Credit can be subject to criminal sanctions and fines in accordance with the provisions of Article 49 (1) of Law No. 10/1998.